HUBUNGAN USIA DAN GRAVIDA TERHADAP KUNJUNGAN ANC - Adriani; Ike Sri Wahyuni (LPPM STIKes Mitra Adiguna, 2023)
Pregnancy midwifery care services are carried out to be able to detect complications in pregnancy and determine the appropriate management of these complications. The decline in MMR and IMR is currently getting worse along with the Covid-19 pandemic since early 2020 until now. Based on the results of reporting data from Local Regional Monitoring (PWS) Maternal and Child Health (KIA) in 2020, the number of first pregnancy visits (K1) has decreased to 91.4% from 99.6% in 2019 and the number of K4 visits only reached 89 .8%. The purpose of this study was to determine whether the age of the mother and gravida had an effect on the visit of Antenatal Care (ANC) at Lismarini Palembang's Independent Midwife Practice (PMB). This type of research is a quantitative research using an analytic survey method with a cross sectional approach. The population of this study was all 3rd trimester pregnant women who had ANC visits at BPM Lismarini Palembang, while the sample was a portion of 3rd trimester pregnant women who had ANC visits at BPM Lismarini Palembang. The sampling technique in this study was carried out by accidental sampling technique. The data analysis used was univariate analysis followed by bivariate analysis. Statistical test results showed that there was no significant relationship between maternal age and ANC visits at BPM Lismarini (p value 1.000) and there was a relationship between gravida and ANC visits at BPM Lismarini (p value 0.048). From the results of the study it can be concluded that the gravida variable is related to antenatal care visits at BPM Lismarini. Keywords: ANC visits, age, gravida.